A study on the mindfulness of tourists/visitors at the Forte do Presépio and Arte Sacra Museums, Belém, PA - Campos, Raul Ivan Raiol de; Cardoso Brabo , Vânia; Oliveira da Silva, Lucas (RITUR - Revista Iberoamericana de Turismo, 2024)
Exhibition evaluation is critical for museums, providing crucial data on the interaction between visitors and the exhibited content. Museums are institutions that collect and exhibit the history and culture of different societies and are one of the main tourist attractions. Therefore, this study aimed to analyze the interaction of tourists/visitors at the Museum of the Forte do Presépio and the Museum of Arte Sacra in Belém - PA, based on the theoretical perspectives of mindfulness by Langer (1989), communication factors and visitor factors by Moscardo (2009), and dual processing by Evans (2008). The methodology consisted of a bibliographic and field research approach, including direct observation and the application of questionnaires to record the data. The results indicate the effectiveness of the communicative and interactive strategies employed at both museums, leading to states of mindfulness in 66% of tourists/visitors. It is concluded that both museums have significant efforts to provide an experience that promotes mindfulness in tourists/visitors, highlighting the importance of exhibition evaluation in promoting mindful interactions. This study also identified the need for improvements in areas such as signage, mediation and design of exhibition content.